Effects of HSD11B1 knockout and overexpression on local cortisol production and differentiation of mesenchymal stem cells - Kragl, Angelique; Schoon, Janosch; Tzvetkova, Ana; Wenzel, Christoph; Blaschke, Martina; Böcker, Wolfgang; Siggelkow, Heide; Tzvetkov, Mladen V. (Frontiers in Bioengineering and Biotechnology, 2022)
Exogenous glucocorticoids increase the risk for osteoporosis, but the role of endogenous glucocorticoids remains elusive. Here, we describe the generation and validation of a loss- and a gain-of-function model of the cortisol producing enzyme 11β-HSD1 (HSD11B1) to modulate the endogenous glucocorticoid conversion in SCP-1 cells - a model for human mesenchymal stem cells capable of adipogenic and osteogenic differentiation. CRISPR-Cas9 was successfully used to generate a cell line carrying a single base duplication and a 5 bp deletion in exon 5, leading to missense amino acid sequences after codon 146. These inactivating genomic alterations were validated by deep sequencing and by cloning with subsequent capillary sequencing. 11β-HSD1 protein levels were reduced by 70% in the knockout cells, thus cortisol production was not detectable. Targeted chromosomal integration was used to stably overexpress HSD11B1. Compared to wildtype cells, HSD11B1 overexpression resulted in a 7.9-fold increase in HSD11B1 mRNA expression, a 5-fold increase in 11β-HSD1 protein expression and 3.3-fold increase in extracellular cortisol levels under adipogenic differentiation. The generated cells were used to address the effects of 11β-HSD1 expression on adipogenic and osteogenic differentiation. Compared to the wildtype, HSD11B1 overexpression led to a 3.7-fold increase in mRNA expression of lipoprotein lipase (LPL) and 2.5-fold increase in lipid production under adipogenic differentiation. Under osteogenic differentiation, HSD11B1 knockout led to enhanced alkaline phosphatase (ALP) activity and mRNA expression, and HSD11B1 overexpression resulted in a 4.6-fold and 11.7-fold increase in mRNA expression of Dickkopf-related protein 1 (DKK1) and LPL, respectively. Here we describe a HSD11B1 loss- and gain-of-function model in SCP-1 cells at genetic, molecular and functional levels. We used these models to study the effects of endogenous cortisol production on mesenchymal stem cell differentiation and demonstrate an 11β-HSD1 dependent switch from osteogenic to adipogenic differentiation. These results might help to better understand the role of endogenous cortisol production in osteoporosis on a molecular and cellular level.